The Global Regulator PhoU Positively Controls Growth and Butenyl-Spinosyn Biosynthesis in Saccharopolyspora pogona - Tang, Jianli; Chen, Jianming; Liu, Yang; Hu, Jinjuan; Xia, Ziyuan; Li, Xiaomin; He, Haocheng; Rang, Jie; Sun, Yunjun; Yu, Ziquan; Cui, Jun; Xia, Liqiu (Frontiers in Microbiology, 2022)
Butenyl-spinosyn, a highly effective biological insecticide, is produced by Saccharopolyspora pogona. However, its application has been severely hampered by its low yield. Recent studies have shown that PhoU plays a pivotal role in regulating cell growth, secondary metabolite biosynthesis and intracellular phosphate levels. Nevertheless, the function of PhoU remains ambiguous in S. pogona. In this study, we investigated the effects of PhoU on the growth and the butenyl-spinosyn biosynthesis of S. pogona by constructing the mutants. Overexpression of phoU increased the production of butenyl-spinosyn to 2.2-fold that of the wild-type strain. However, the phoU deletion resulted in a severe imbalance of intracellular phosphate levels, and suppression of the growth and butenyl-spinosyn biosynthesis. qRT-PCR analysis, distinctive protein detection and mass spectrometry revealed that PhoU widely regulated primary metabolism, energy metabolism and DNA repair, which implied that PhoU influences the growth and butenyl-spinosyn biosynthesis of S. pogona as a global regulator.